(untitled) (Medico Legal Update, 2021)
Diabetes claims millions of lives every year. Diabetes Mellitus is a metabolic disorder that occurs due to the increase in blood sugar level. The blood sugar level control by insulin secreted from pancreas. The diabetes classify as type 1 and type 2 depending on insulin secretion. The type 2 diabetes is more common in people than type 1 diabetes. Traditionally, the blood glucose level estimate with glucometer and blood test. However, the test require invasive blood pricking for blood glucose measurement. The measured blood glucose value also varies due to amount of blood taken for testing, part of blood used for testing, depth of finger pricking, physical activity, stress and underlying illness. Hence, the insulin secretion from pancreas monitor for accurate prediction of blood glucose level. The blood glucose level varies with respect to insulin secretion from pancreas. In this paper, we propose a non-invasive approach to estimate blood glucose accurately through NIR spectroscopy for diabetes control. The NIR spectroscopy signal obtained from pancreas process through Rational Dilation Wavelet Transformto determine the insulin secretion level. The non-invasive NIR spectroscopy method measures glucose level with 90% accuracy compared to lab results.